2017
DOI: 10.1523/jneurosci.2712-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Differential Presynaptic ATP Supply for Basal and High-Demand Transmission

Abstract: The relative contributions of glycolysis and oxidative phosphorylation to neuronal presynaptic energy demands are unclear. In rat hippocampal neurons, ATP production by either glycolysis or oxidative phosphorylation alone sustained basal evoked synaptic transmission for up to 20 min. However, combined inhibition of both ATP sources abolished evoked transmission. Neither action potential propagation failure nor depressed Ca 2ϩ influx explained loss of evoked synaptic transmission. Rather, inhibition of ATP synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 56 publications
1
65
1
Order By: Relevance
“…Thus, the absence of distal mitochondria may contribute to the lower efficiency of distal neuropeptide release and endocytosis that occurs as part of the SSV cycle (Fig. 2), which is known to be affected by mitochondria under high demand conditions (Rangaraju et al, 2014;Pathak et al, 2015;Sobieski et al, 2017). Together, the results presented here demonstrate deficient accumulation of two types of organelles -DCVs and mitochondria -and attenuated synaptic function at the most distal sites of extensive monoaminergic innervation.…”
Section: Mitochondrial Distribution and Synaptic Neuropeptide Releasementioning
confidence: 63%
See 1 more Smart Citation
“…Thus, the absence of distal mitochondria may contribute to the lower efficiency of distal neuropeptide release and endocytosis that occurs as part of the SSV cycle (Fig. 2), which is known to be affected by mitochondria under high demand conditions (Rangaraju et al, 2014;Pathak et al, 2015;Sobieski et al, 2017). Together, the results presented here demonstrate deficient accumulation of two types of organelles -DCVs and mitochondria -and attenuated synaptic function at the most distal sites of extensive monoaminergic innervation.…”
Section: Mitochondrial Distribution and Synaptic Neuropeptide Releasementioning
confidence: 63%
“…Interestingly, endocytosis for SSV recycling and 'kiss-and-run' exocytosis for synaptic neuropeptide release both involve dynamin (Holz, 2013;Wong et al, 2015). Furthermore, in part because of dynamin, SSV recycling is a major consumer of ATP, which is provided by mitochondria when transmission is intense (Rangaraju et al, 2014;Pathak et al, 2015;Sobieski et al, 2017). Therefore, it will be of interest to test the hypothesis that the lower abundance of distal mitochondria limits dynamin function to diminish both endocytosis and neuropeptide release.…”
Section: Function Of Distal Type II Boutonsmentioning
confidence: 99%
“…These studies demonstrate that both glycolysis and oxphos contribute to presynaptic function by generating ATP in an activity‐dependent manner. Similarly, Sobieski et al found that simultaneous inhibition of both glycolysis and oxphos is required to achieve complete inhibition of evoked synaptic transmission (Sobieski, Fitzpatrick, & Mennerick, ). Therefore, it is likely that both oxphos and aerobic glycolysis contribute to synaptic energy metabolism and offer redundancies that confer energetic flexibility for synaptic activity.…”
Section: Axonal Atp Production and Maintenancementioning
confidence: 95%
“…These studies demonstrate that both glycolysis and oxphos contribute to presynaptic function by generating ATP in an activity-dependent manner. Similarly, Sobieski et al found that simultaneous inhibition of both glycolysis and oxphos is required to achieve complete inhibition of evoked synaptic transmission (Sobieski, Fitzpatrick, & Mennerick, 2017).…”
Section: Presynaptic Atp Production In Maintaining Synaptic Transmimentioning
confidence: 96%
See 1 more Smart Citation